Ergonomics in careers dedicated to rhinoplasty: prevalence and prevention of work-related musculoskeletal disorders - Santos, Mariline; Bulut, Cem; Hohenberger, Ralph; Vergeer, Rob; Gonçalves Ferreira, Miguel; Datema, Frank R (Aesthetic surgery journal, 2025)
Rhinoplasty is an ergonomically demanding procedure that subjects surgeons to prolonged unfavorable postures and repetitive fine motor movements, increasing the risk of work-related musculoskeletal disorders (WRMDs). Nevertheless, ergonomic awareness and training in rhinoplasty remain limited.The aim of the authors of this study is to evaluate the prevalence of WRMDs among rhinoplasty surgeons and to assess ergonomic factors, training, and attitudes toward strategies to improve well-being and career longevity.A 36-item electronic survey was distributed to members of the Evidence-Based Rhinoplasty Research Group (Feb-May 2025) to gather demographic, professional, and ergonomic data, including Likert-scale assessments of comfort and strain during rhinoplasty.A total of 109 consultant surgeons completed the survey. Mean comfort and strain scores were 6.7±1.7 and 5.2±2.3, respectively; 72% experienced discomfort (mainly neck, shoulders, and lower back), with greater experience correlating with better scores (P < .05). No significant differences were observed with gender, BMI, height, average duration of each rhinoplasty, weekly time spent on rhinoplasty, or the use of headlights or loupes. Only 5.3% had received formal ergonomics training; however, 81.4% expressed interest in ergonomic assessments, and 93.8% believed exercise benefits career longevity.WRMDs are highly prevalent among rhinoplasty surgeons. Comfort and strain appear more related to posture, case volume, and cumulative experience than to specific instruments or techniques. Despite the prevalence and impact of these symptoms, ergonomic training remains rare, although interest is high. Targeted interventions—such as optimizing operating room setup, promoting intraoperative microbreaks, and encouraging physical exercise—are essential to reduce discomfort and support long-term career sustainability.